2021
DOI: 10.1111/jan.15048
|View full text |Cite
|
Sign up to set email alerts
|

Triage assessment of transitory loss of consciousness in the emergency department—A retrospective observational study

Abstract: Aim: To establish how the Manchester Triage System can correctly prioritize patients admitted to the emergency department for transitory loss of consciousness in relation to their risk of presenting severe acute disease. Design: A observational retrospective study. Methods: A total of 2291 patients who required a triage evaluation for a transitory loss of consciousness at the emergency department of Merano Hospital between 1 January 2017 and 30 June 2019 were considered. Transitory loss of consciousness was cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…While the deficits in concordance may be partly due to an excessive attempt of the triage systems to aim at an exhausting search for standardization and simplification even of heterogeneous and complex clinical presentations, the need to combine this strictly objective methodology of the triage systems with the advantage of the clinical experience of the individual nurse and his learning pathway in clinical practice may also emerge. Therefore, the daily triage audit could be part of the latter, stimulating continuous professional growth and the attainment of experience based on the comparison that could refine the schematic nature of triage systems even in those complex presentations that are difficult to harness within specific diagrams or flow‐charts based on symptoms (Ausserhofer et al, 2020; Zaboli, Ausserhofer, Sibilio, Paulmichl, Toccolini, Pfeifer, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While the deficits in concordance may be partly due to an excessive attempt of the triage systems to aim at an exhausting search for standardization and simplification even of heterogeneous and complex clinical presentations, the need to combine this strictly objective methodology of the triage systems with the advantage of the clinical experience of the individual nurse and his learning pathway in clinical practice may also emerge. Therefore, the daily triage audit could be part of the latter, stimulating continuous professional growth and the attainment of experience based on the comparison that could refine the schematic nature of triage systems even in those complex presentations that are difficult to harness within specific diagrams or flow‐charts based on symptoms (Ausserhofer et al, 2020; Zaboli, Ausserhofer, Sibilio, Paulmichl, Toccolini, Pfeifer, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The growing number of patients affects triage, forcing patients with varying conditions to wait for hours, potentially leading to a loss of consciousness [2]. Loss of consciousness is a common and serious indicator that requires high-priority triage [3,4]. When a patient loses consciousness, he or she becomes unbalanced, which result in falls.…”
Section: Introductionmentioning
confidence: 99%
“…Many solutions were proposed, one solution is to use AI techniques. Many medical studies have suggested the use of digital triage systems and their enhancement through the application of arti cial intelligence techniques [3,4,[11][12][13]. Nevertheless, the use of ML and DL is expected to gradually spread in healthcare to include all medical specialties [5,14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, different studies have focused on evaluating the performance of MTS on individual symptom presentations, reporting conflicting results about its ability. While some studies have demonstrated a good ability of MTS to correctly identify and stratify certain symptoms and specific pathologies (e.g., chest pain, headache, and dyspnea), for other symptoms it has revealed a lower ability to prioritize patients with time‐dependent pathologies (e.g., cardiac syncope and pulmonary embolism) 7,8,10–13 …”
Section: Introductionmentioning
confidence: 99%
“…While some studies have demonstrated a good ability of MTS to correctly identify and stratify certain symptoms and specific pathologies (e.g., chest pain, headache, and dyspnea), for other symptoms it has revealed a lower ability to prioritize patients with time-dependent pathologies (e.g., cardiac syncope and pulmonary embolism). 7,8,[10][11][12][13] Difficulties in promptly and accurately recognizing TGA in the ED setting during the triage process could lead to incorrect priority codes assigned to patients (overtriage), resulting in inappropriate use of resources. The study aims to analyze the performance of MTS in the assessment of patients with a diagnosis of TGA.…”
mentioning
confidence: 99%